1999
DOI: 10.1161/01.res.85.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Scavenger Receptor Class B Type I in Cultured Human Monocyte-Derived Macrophages and Atherosclerotic Lesions

Abstract: Abstract-The scavenger receptor class B type I (SR-BI) and its human homologue CLA-1 (CD36 and LIMPII Analogous-1) have recently been identified to bind HDL and mediate the selective uptake of HDL lipids. Tissue distribution of both murine and human receptors is quite similar, in that they are expressed abundantly in liver and steroidogenic tissues. However, expression and function of the human SR-BI (hSR-BI), in the periphery of reverse cholesterol transport such as macrophages, are still unclear. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
118
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 37 publications
4
118
2
Order By: Relevance
“…Alternatively, its function in the uptake of modified lipoproteins might promote foam cell formation, rendering macrophage SCARB1 a proatherogenic factor. Previous in vitro studies have shown that oxLDL-induced changes in SCARB1 mRNA expression may be dependent on the differentiation status of the investigated cells, with transcription upregulated in the early differentiation stage [40,41] and downregulated in fully differentiated macrophages [11,40]. The lack of difference in the rates of SCARB1 expression stimulated by LDL from NGT and IGT subjects in the present study suggests that, in contrast to CD36, macrophage expression of SCARB1 is less sensitive to changes in LDL glycoxidation status.…”
Section: Discussioncontrasting
confidence: 43%
“…Alternatively, its function in the uptake of modified lipoproteins might promote foam cell formation, rendering macrophage SCARB1 a proatherogenic factor. Previous in vitro studies have shown that oxLDL-induced changes in SCARB1 mRNA expression may be dependent on the differentiation status of the investigated cells, with transcription upregulated in the early differentiation stage [40,41] and downregulated in fully differentiated macrophages [11,40]. The lack of difference in the rates of SCARB1 expression stimulated by LDL from NGT and IGT subjects in the present study suggests that, in contrast to CD36, macrophage expression of SCARB1 is less sensitive to changes in LDL glycoxidation status.…”
Section: Discussioncontrasting
confidence: 43%
“…SAA uptake into macrophages is strongly dependent on cell surface heparan sulfate binding to SAA (41) and occurs via a clathrin-dependent pathway (41). SR-BI is expressed in activated macrophages (42), but its contribution in these cells to HDL-selective lipid uptake, or SAA uptake, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, SR-BI contributes to cellular cholesterol efflux from peripheral tissues, the first step during reverse cholesterol transport. SR-BI is also present in monocyte/macrophages including THP-1 cells (30), where it could function as a true ox-LDL receptor by displaying many of the features characteristic for classical scavenger receptors including uptake and degradation of oxidized lipoproteins (66). Braun and co-workers (67) report that the loss of SR-BI expression leads to the early onset of occlusive atherosclerotic coronary artery disease, spontaneous myocardial infarctions, severe cardiac dysfunction, and premature death in apolipoprotein E-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…29). Although SR-BI in comparison to SR-A and CD36 is less abundant in atherosclerotic lesions, its mRNA expression pattern during differentiation of human macrophages is similar to SR-AI and CD36, and both Cu-ox-LDL and ac-LDL may up-regulate its expression (30). Previous studies suggested that the primary routes for entry of ligands by macrophages are coated pits or caveolin-dependent endocytosis and/or phagocytosis.…”
mentioning
confidence: 92%